Nanocarriers and macrophage interaction: from a potential hurdle to an alternative therapeutic strategy - Naths Grazia Sukubo; Paolo Bigini; Annalisa Morelli (Beilstein Journal of Nanotechnology)
In the coming decades, the development of nanocarriers (NCs) for targeted drug delivery will mark a significant advance in the field of pharmacology. NCs can improve drug solubility, ensure precise distribution, and enable passage across biological barriers. Despite these potential advantages, the interaction with many biological matrices, particularly with existing macrophages, must be considered. In this review, we will explore the dual role of macrophages in NC delivery, highlighting their physiological functions, the challenges posed by the mononuclear phagocyte system, and innovative strategies to exploit macrophage interactions for therapeutic advantage. Recent advancements in treating liver and lung diseases, particularly focusing on macrophage polarization and RNA-based therapies, have highlighted the potential developments in macrophage–NC interaction. Furthermore, we will delve into the intriguing potential of nanomedicine in neurology and traumatology, associated with macrophage interaction, and the exciting possibilities it holds for the future.